tsRNAs: Novel small molecules from cell function and regulatory mechanism to therapeutic targets - Zong, Tingyu; Yang, Yanyan; Zhao, Hui; Li, Lin; Liu, Meixin; Fu, Xiuxiu; Tang, Guozhang; Zhou, Hong; Aung, Lynn Htet Htet; Li, Peifeng; Wang, Jianxun; Wang, Zhibin; et al. (Cell proliferation, 2021)
tsRNAs are small fragments of RNAs with specific lengths that are generated by particular ribonucleases, such as dicer and angiogenin (ANG), clipping on the rings of transfer RNAs (tRNAs) in specific cells and tissues under specific conditions. Depending on where the splicing site is, tsRNAs can be segmented into two main types, tRNA‐derived stress‐induced RNAs (tiRNAs) and tRNA‐derived fragments (tRFs). Many studies have shown that tsRNAs are functional molecules, not the random degradative products of tRNAs. Notably, due to their regulatory mechanism in regulating mRNA stability, transcription, ribosomal RNA (rRNA) synthesis and RNA reverse transcription, tsRNAs are significantly involved in the cell function, such as cell proliferation, migration, cycle and apoptosis, as well as the occurrence and development of a variety of diseases. In addition, tsRNAs may represent a new generation of clinical biomarkers or therapeutic targets because of their stable structures, high conservation and widely distribution, particularly in the peripheral tissues, bodily fluids and exosomes. In this review, we describe the generation, function and mechanism of tsRNAs and illustrate the current research progress of tsRNAs in various diseases, highlight their potentials as biomarkers and therapeutic targets in clinical application. Although our understanding of tsRNAs is still in infancy, the application prospects shown in this field deserve further exploration. tsRNAs are generated under stress condition which are functional molecules. Due to their regulatory mechanism in regulating mRNA stability, transcription, ribosomal RNA (rRNA) synthesis and RNA reverse transcription, tsRNAs are significantly involved in the cellular function, including cell proliferation, migration, cell cycle and apoptosis, as well as the occurrence and development of a variety of diseases.